Towards a New Curriculum: The DEREC Experience - Tuneski, Atanasko; CAPORALI, ENRICA (Proceedings e report, 2009)
This volume presents the experience of developing a new undergraduate curriculum on "Environmental and Resources Engineering" at the Ss. Cyril and Methodius University of Skopje in FYR Macedonia, in the framework of the TEMPUS CD_JEP_19028_2004 DEREC - Development of Environmental and Resources Engineering Curriculum (2005-2008). This publication describes the methodology, instruments and processes employed in the curriculum development. It is divided into two main parts. The first part describes the European Consortium approach (including papers from all representatives of Consortium Member institutions in the European Union and the external project experts). The second part describes the approach adopted by the various faculty representatives of the Ss. Cyril and Methodius University in Skopje and the South East European University of Tetovo, in FYR Macedonia. This book is designed to serve as an updated, coherent and concrete set of instruments for the achievement of similar project objectives.